The construction of the social place of women in cordel: An analysis of the novel the evil in pay of good, by Leandro Gomes de Barros (Research, Society and Development, 2020)
This paper aims to reflect on the representation of the social place of women in popular literature, taking as its starting point the analysis of the cordel literature booklet O mal em paga do bem ou Rosa e Lino de Alencar, by Leandro Gomes de Barros. This is a bibliographic and qualitative research that has investigated how the social environment experienced by the author has influenced the construction of the characters in the narrative. The women representation on the string book is analyzed in the light of the Brazilian socio-historical context in the pre-industrial period. As theoretical support for this research, the concept of “historical mentality of a time”, developed by Lee Goff (2003), the studies on “the new woman”, by Hobsbawm (1988), and the reflections of Pierre Bourdieu (2019) about symbolic power should be highlighted. It can be affirmed that the poet reproduces on the character Rosa the concept of woman from pre-industrial societies, portraying her in the role of housewife, mother, educator and, at the same time, narrating incipient forms of female emancipation constructions. In summary, the poet does not create, does not idealize, he only reproduces the image of the woman of his time.